2015
DOI: 10.1590/1807-1929/agriambi.v19n12p1152-1158
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency of coriander produced in a low-cost hydroponic system

Abstract: A B S T R A C TThe increase of water use efficiency in crop production is a clear need in areas with restricted access to this resource and, in these cases, the adoption of forms of cultivation contextualized to local conditions are essential. Thus, the implications of the variation in the amount of seeds per cell (0.5, 1.0, 1.5 and 2.0 g) and spacing between cells (7.0, 10.0 and 15.0 cm) on variables related to consumption and water use efficiency for the production of coriander (cv. Tabocas) in a low-cost hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
6
0
4
Order By: Relevance
“…Reduction in water consumption for nutrient solutions prepared in saline waters has already been observed for lettuce (Paulus et al, 2012), coriander (Santos Júnior et al, 2015) and other vegetables (Silva et al, 2012). In all of these cases, the increase in ECns was associated with the reduction in the osmotic potential.…”
Section: Resultsmentioning
confidence: 66%
“…Reduction in water consumption for nutrient solutions prepared in saline waters has already been observed for lettuce (Paulus et al, 2012), coriander (Santos Júnior et al, 2015) and other vegetables (Silva et al, 2012). In all of these cases, the increase in ECns was associated with the reduction in the osmotic potential.…”
Section: Resultsmentioning
confidence: 66%
“…The SFM bunch production obtained in the present study is consistent with those reported in other studies under hydroponic conditions. Santos Júnior et al (2015) obtained a SFM production of 45.44 g bunch -1 of coriander cv. 'Tabocas' , considering a sowing density of 0.5 g of seeds per cultivation cell at 28 DAS, and Silva et al (2016) found production of 50.33 g bunch -1 of 12 coriander plants cv.…”
Section: Resultsmentioning
confidence: 99%
“…NFT is an active system which assumes pumping for nutrient solution recirculation, performing irrigations usually at 0.25 h intervals (15 min) (Zanella et al, 2008). Since it depends on electricity, the expansion of hydroponics may be limited in sites where the infrastructure is inadequate to conduct electricity, which leads to inconsistency in its supply (Santos Júnior et al, 2015;Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resultados de pesquisas (Cazuza Neto et al, 2014;Santos Júnior et al, 2015;Silva et al, 2016) Como geralmente as chuvas concentram-se entre três e quatro meses, com base no conhecimento da necessidade hídrica de uma planta pode-se calcular o volume necessário de água para manter a produção de cada mês, como isso uma opção seria armazenar água das chuvas para suprir a produção no período de seca. Outra opção seria o uso diretamente de águas salobras.…”
Section: Introductionunclassified